Pengembangan E-Modul Akuntansi Perusahaan Dagang Berbasis Instalasi Android Untuk Meningkatkan Kemandirian dan Hasil Belajar Peserta Didik - Ihsan Ihsan; Hully Hully (Universitas Hamzanwadi, 2023)
This study aims to produce learning media in the form of e-modules based android in the form of applications and test their effectiveness in increasing student independence and learning outcomes. The development research method uses the ADDIE model with field test design a quasi-experimental one-group pretest-posttest. The test subjects were 29 students. Data analysis used the n-gain score and paired sample test statistics. The results showed that, (1) the developed Android-based e-module learning media was very suitable to be used as an accounting learning medium based on the validation results of material experts of 91.10%, media experts of 89.67%, and supported by student responses that were very good at 87.64%. (2) the android-based e-module learning media is very effective and has a significant effect on increasing student learning independence, as evidenced by the average score after the application of the media is 87.76 with a normalized gain value of 0.71 high criteria and statistical test results sig. 0.00 < 0.05. (3) the android-based e-module learning media is very effective and has a significant effect on improving student learning outcomes, as evidenced by the average score after the application of the media is 89.63 with a normalized gain value of 0.73 high criteria and reinforced by the sig statistical test results. 0.00 < 0.05. Besides that, the application of Android-based e-module learning media is very possible for students to increase motivation and critical thinking skills.